Estrategia de personal branding a través de inbound marketing y marketing viral para generar engagement al canal de un youtuber en Quito. Caso: Gabriela Navas. - Navas Espinosa, María Gabriela (2016)
The video consumption on internet has expanded in the last few years and the YouTube platform has been involved in the audiovisual content spread since 2005. From that point on, it has started a new generation of online communicators called Youtubers, who not only create atractive content for a faithful audience, but also create an online business based on video reproductions by ads. The main objective is to develop a Personal Branding strategy by Inbound Marketing and Viral Marketing, aslo called viral buzz, in order to create an engagement to a Youtube channel in Quito. The Personal Brand applied in this project is the Ecuadorian youtuber Gabriela Navas. One of the theorist sources mentioned for the development of the strategy is Personal Branding; which has the purpose to promote the youtubers brand image. It is fundamental to use online tools and create attractive content to reach the target by promoting their interest to share and interact with the content, which is called Viral Marketing as a consequence of the Inbound Marketing. The fundamental part of this project was to investigate the behaviors and interest of Gabrielas target to identify what content they are looking for in a new YouTube entertainment channel and their reasons for the content preference. The discoveries that were made were that Post Milliennials are searching for something new and innovative on YouTube. It is important to create close bonds with the audience because the suscribers are going to be the voice of the Brand. They can also become a Youtuber into a lovemark. All of this will bring awarness and engagement with the target. Therefore, in this document there are digital, marketing and online advertising strategies for a personal Brand management based on the creation of quality content for the audience, with the objective that the audience becomes a means of communication for the youtuber, having branding on social media and succesful search engine optimization.